PENERAPAN TEKNOLOGI PROSES PENCAMPURAN SEMI REFINED CARRAGEENAN (SRC) DAN REFINED CARRAGEENAN (RC) RUMPUT LAUT MERAH (Kappaphycus alvarezii) TERHADAP KARAKTERISTIKFISIKO-KIMIA KARAGINAN - Aidil Fadli Ilhamdy; Jumsurizal, Jumsurizal; Shabilla, Wan Kirana (Marinade, 2019)
This study aims to determine the application of the mixing process technology of semi-refined carrageenan and refined carrageenan Kappaphycus alvarezii to the physicochemical properties of carrageenan to obtain simpler process technology but with quality products that are by carrageenan standards. Determination of the best mixing technology was carried out in several stages, refined carrageenan, and the semi-refined carrageenan and refined carrageenan mixing process technology, then followed by Physico-chemical analysis, yield, moisture content, ash content, acid insoluble ash content, gel strength, viscosity, melting point, and cumulative point. The best results on carrageenan which quality standard characteristics, namely gel strength 376,46 g/cm2, viscosity 139,47 cP, melting point 55,70 ÂºC, and the point of departure 38.00 ÂºC